2018
DOI: 10.1101/375642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcome contingency selectively affects the neural coding of outcomes but not of tasks

Abstract: 27Humans make choices every day, which are often intended to lead to desirable outcomes. While we often 28 have some degree of control over the outcomes of our actions, in many cases this control remains limited. 29Here, we investigate the effect of control over outcomes on the neural correlates of outcome valuation 30 and implementation of behavior, as desired outcomes can only be reached if choices are implemented as 31 intended. In a value-based decision-making task, reward outcomes were either contingent o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Reward expectation boosts cue-locked activity across the FP network (Parro et al, 2018), and it has been recently linked to stronger anticipatory rule encoding (Etzel et al, 2016). Nonetheless, contradictory findings have also been observed (Wisniewski et al, 2019), and a comprehensive characterization of this interaction in complex, novel scenarios is still pending. Consequently, we included economic incentives in our paradigm and assessed the nature of their effect on instruction preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Reward expectation boosts cue-locked activity across the FP network (Parro et al, 2018), and it has been recently linked to stronger anticipatory rule encoding (Etzel et al, 2016). Nonetheless, contradictory findings have also been observed (Wisniewski et al, 2019), and a comprehensive characterization of this interaction in complex, novel scenarios is still pending. Consequently, we included economic incentives in our paradigm and assessed the nature of their effect on instruction preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these findings, it has been shown that in the Stroop task a cue indicating high efficacy improves behavioral performance (Dean Wolf, Cory, & Shenhav, 2018). At the neural level it has been shown that higher perceived efficacy increases the value of outcomes (Wang & Delgado, 2019) and strengthens their representation in the brain network including the striatum, prefrontal and parietal cortex (Wisniewski, Forstmann, & Brass, 2019). While there is initial evidence to support the role of efficacy in the allocation of cognitive effort, the neural dynamics through which efficacy estimates are formed and the way in which they influence the allocation of cognitive control remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Reward expectation boosts cue-locked activity across the FP 93 network (Parro, Dixon, & Christoff, 2017), and it has been recently linked to stronger anticipatory 94 rule encoding (Etzel, Cole, Zacks, Kay, & Braver, 2016). Nonetheless, contradictory findings 95 have also been found (Wisniewski, Forstmann, & Brass, 2018), and a comprehensive 96 characterization of this interaction in complex, novel scenarios is still pending. Consequently, we 97 included economic incentives in our paradigm and assessed the nature of their effect on 98 instruction preparation.…”
mentioning
confidence: 99%